Middle Transnistria in structure national ecological network of Ukraine: state and prospects of development - Mudrak, Olexandr; Mudrak, Galina; Bryndak, Тetiana (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The paper analyzes the structure of the Middle Transnistria national ecological network. The scheme of regional ecological network with the release of its structural elements. Showing prospects of development by 2020.
Keywords: biological and landscape diversity; Middle Transnistria; regional ecological network; scheme; structural elements